O discurso sobre a morte em arquivos institucionais do final do século XIX - Pedrazzi, Fernanda Kieling (2015)
This study aimed to investigate discourse about death in institutional archives (re)visited to collect sources of research. The theoretical question revolves around discourse about . Theories and concepts from the area Linguistics, Letters and Arts and basic area Linguistics make up the theoretical basis, with an emphasis on the French School of Discourse Analysis. The area of Applied Social Sciences , basic area Information Sciences, is also contemplated in order to account for issues of archiving and information. Springing from these disparate fields, Archiving and Discourse Analysis, we attempted to read and analyze the selected materiality, by creating a temporal and chronological framework, with a focus on the city of Santa Maria, RS, and taking the year 1896 as a reference for the deaths. Data collected consisted of: 1) death certificates produced/received by the Municipal Intendance and kept at the Municipal Historical Archive of Santa Maria; 2) death records recorded at the Cathedral and kept in the archdiocese archive; and 3) death records made at the Registry Office. Two hundred and seventy-five reports of death were found for 1896, with the Municipal Intendance of Santa Maria (167), having the greatest number, followed by the catholic cathedral (64) and, finally, the Registry Office of Santa Maria (44). A comparison among the three sets was performed, to obtain a total of 197 names of different people. The names of the deceased with reports common to all three entities made up the empirical corpus (12 deaths and respective reports). The study considered death notices, news articles and personal accounts or tributes published in the newspaper regarding these deaths extracted from a local newspaper that circulated during the year studied, as well as a postmortem inventory, the only one of its kind found, which made part of the Public Archive of the State of Rio Grande do Sul. Using discourse analysis, extracts from the discursive field were used to demonstrate the five domains of discourse about death, elected from their incidence: medical, religious, judicial, journalistic and private discourse, proposed in this dissertation as a new category. Discursive sequences that made up the corpus were analyzed within these discourses about death. The perception of the meaning of words within language use and the relation between historicity and discourse are constants in the corpus.